Self-portrait with ghost : short stories - Jin, Meng, 1989- (Mariner Books, 2022)
"From the acclaimed author of Little Gods, whose 'gift merges science, politics and art: the kind of audacity our world needs now' (Gina Apostol), comes an immersive and electrifying story collection that explores self-construction, female resilience, and migrations both literal and transformative"--